2016
DOI: 10.1016/j.ejca.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide pharmacokinetics and pharmacogenetics in children with B-cell non-Hodgkin's lymphoma

Abstract: IntroductionVariation in cyclophosphamide pharmacokinetics and metabolism has been highlighted as a factor that may impact on clinical outcome in various tumour types. The current study in children with B-cell non-Hodgkin's lymphoma (NHL) was designed to corroborate previous findings in a large prospective study incorporating genotype for common polymorphisms known to influence cyclophosphamide pharmacology.MethodsA total of 644 plasma samples collected over a 5 year period, from 49 B-cell NHL patients ≤18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 25 publications
3
44
0
Order By: Relevance
“…Ifosfamide metabolism by CYP2B6.1 is enantioselective, but stereoselectivity with CYP2B6 variants is unknown. Cyclophosphamide hydroxylation by CYP2B6.6 was greater than CYP2B6.1 in vitro , but this was not apparent clinically . The influence of CYP2B6 polymorphisms and stereochemistry on human ifosfamide and cyclosphosphamide metabolism is unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Ifosfamide metabolism by CYP2B6.1 is enantioselective, but stereoselectivity with CYP2B6 variants is unknown. Cyclophosphamide hydroxylation by CYP2B6.6 was greater than CYP2B6.1 in vitro , but this was not apparent clinically . The influence of CYP2B6 polymorphisms and stereochemistry on human ifosfamide and cyclosphosphamide metabolism is unknown.…”
Section: Discussionmentioning
confidence: 98%
“…This study did not assess CYP2C19 . In contrast, in children (mean age 11.2 ± 4 years) with non‐Hodgkins lymphoma ( n = 49) an association was observed between the CYP2B6*6 allele and lower clearance of cyclophosphamide both at dose 1 and at dose 5 (after autoinduction) . No association was found in this study with CYP2C19*2 .…”
Section: Plasma Pharmacokineticsmentioning
(Expert classified)
“…It is clear that the majority of the therapeutic outcome or pharmacokinetic studies have focussed on CYP2B6 and/or CYP2C19 as candidate genes. However, some studies have also reported on selected SNP in other candidate genes such as CYP2C9 , GST or ABCB1 . Whilst not the focus of this review, it is important to note that the role of pharmacogenetics in the risk of excessive toxicity (due to high levels of bioactivation of this cytotoxic drug) have also been assessed.…”
Section: Therapeutic Outcomesmentioning
confidence: 99%
“…Although the (R)‐(+) and (S)‐(–) enantiomers may differ in their therapeutic responses and toxic effects, the clinical consequences of these differences have not been adequately established. The results of clinical studies investigating enantioselectivity in the kinetic disposition of cyclophosphamide are inconclusive, do not evaluate the individual enantiomers of the active metabolite 4‐hydroxycyclophosphamide, do not evaluate the individual enantiomers of the metabolite carboxyethylphosphoramide mustard, which exposure is related to outcome disease, and involve a small number of patients in different disease states and treated with different combinations of drugs …”
mentioning
confidence: 99%
“…The pharmacokinetics of cyclophosphamide and its metabolites, 4‐hydroxycyclophosphamide and carboxyethylphosphoramide mustard, as an enantiomeric mixture is well defined for the cyclophosphamide intravascular administration in high dose (continuous or daily dosing) to patients with cancer . However, there are no data on the enantioselective kinetic disposition and metabolism of cyclophosphamide in patients with chronic inflammatory autoimmune diseases such as multiple sclerosis and systemic sclerosis.…”
mentioning
confidence: 99%